EVALUASI PEMBINAAN OLAHRAGA TAEKWONDO DI DOJANG THE KICK FIGHTER DENGAN METODE CIPP - Bumulo, Ishar; Samin, Giofandi; Fataha, Iwan; Gani, Ardin Abdul (Plyometric: Jurnal Sains dan Pendidikan Keolahragaan, 2025)
Taekwondo is developing rapidly in Indonesia, but coaching at the dojang level needs to be evaluated for greater effectiveness. This study aims to evaluate Taekwondo coaching at The Kick Fighter Dojang using the CIPP (Context, Input, Process, Product) model. The method used was is a qualitative descriptive through observation, documentation and interviews with 1 administrator, 3 coaches, 10 athletes and 2 parents as well as documentation. The results indicate that the coaching objectives meet the athletes' needs, but there are still shortcomings in the facilities and training program. The coaching process is progressing well, despite constraints on time and training intensity. The coaching products demonstrate good athlete performance at the regional level, but need to be improved at the national level. This study provides an overview of the state of Taekwondo coaching at the dojang and provides recommendations for future improvements.